Reversible electrochemical conversion from selenium to cuprous selenide. Issue 82 (21st September 2021) - Sandstrom, Sean K.; Jiang, Heng; Lucero, Marcos; Xu, Yunkai; Gallagher, Trenton C.; Cao, Mengyuan; Feng, Zhenxing; Ji, Xiulei
Abstract : Using elemental selenium as an electrode, the redox-active Cu 2+ /Cu + ion is reversibly hosted via the sequential conversion reactions of Se → CuSe → Cu3 Se2 → Cu2 Se. Abstract : Using elemental selenium as an electrode, the redox-active Cu 2+ /Cu + ion is reversibly hosted via the sequential conversion reactions of Se → CuSe → Cu3 Se2 → Cu2 Se. The four-electron redox process from Se to Cu2 Se produces a high initial specific capacity of 1233 mA h g −1 based on the mass of selenium alone or 472 mA h g −1 based on the mass of Cu2 Se, the fully discharged product.